The walking dead. Vol. 16, A larger world - Kirkman, Robert (Kirkman, Robert. Walking dead., 2012)
"The world we know is gone...In a matter of months society has crumbled, no government, no grocery stores, no mail delivery, no cable TV. In a world ruled by the dead, we are forced to finally start living."--P. [4] of cover.